2021
DOI: 10.2459/jcm.0000000000001209
|View full text |Cite
|
Sign up to set email alerts
|

Physical performance status predicts mortality in aging patients undergoing pacemaker implantation

Abstract: Aims To assess whether frailty or reduced physical performance status may have an impact on clinical outcomes after pacemaker implantation in aging patients.Methods A prospective cohort of patients aged more than 70 years, admitted to the hospital for pacemaker implantation, was enrolled. Patients were evaluated with the Short Physical Performance Battery (SPPB) and Handgrip Strength Test at hospital discharge and at 1 year. Overall mortality was the primary study endpoint.Results Out of the 119 patients, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…More recently, heart failure, chronic obstructive pulmonary disease, age, syncope, insulin-dependent diabetes mellitus and male gender have been found to be independent predictors of increased mortality in a cohort of 154 PM patients implanted due to a heart block [ 39 ]. Balla et al [ 40 ] reported a mortality rate of 31% in a cohort of 119 PM patients aged more than 70 years and prospectively followed them for 46 months. Reduced physical performance assessed using the short physical performance battery test was independently associated with death during follow-up and the composite of death and rehospitalization at 1-year.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, heart failure, chronic obstructive pulmonary disease, age, syncope, insulin-dependent diabetes mellitus and male gender have been found to be independent predictors of increased mortality in a cohort of 154 PM patients implanted due to a heart block [ 39 ]. Balla et al [ 40 ] reported a mortality rate of 31% in a cohort of 119 PM patients aged more than 70 years and prospectively followed them for 46 months. Reduced physical performance assessed using the short physical performance battery test was independently associated with death during follow-up and the composite of death and rehospitalization at 1-year.…”
Section: Discussionmentioning
confidence: 99%
“…In many countries, there are lots of measurable items of physical function for their citizens. In recent years, there has been a great deal of clinical and research interest in sarcopenia and frailty as a means of evaluating prediction of the event [1][2][3][4]. As for evaluation of sarcopenia and frailty, many theories have been proposed to relate them to various evaluation methods [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…4 Balla et al 6 report on the long-term follow-up (median 46 months) of a group of 119 patients older than 70 years, admitted to hospital for pacemaker implantation and accurately evaluated with regard to frailty through the Short Physical Performance Battery (SPBB) test and handgrip test at discharge and 1-year follow-up. 6 A reduced performance at SPBB was quite common (71% of patients at discharge) and predictive of long-term mortality and the composite endpoint of hospitalization or death, even after adjustment for pertinent confounders at 1 year. It is noteworthy that mortality at the end of follow-up was relevant (31% of enrolled patients) and that no association was found between muscle strength at the handgrip test and mortality.…”
mentioning
confidence: 99%
“…5 Among elderly patients with documented severe coronary artery disease or heart failure, the prevalence of frailty was found to be 50-54% in a metaanalysis and was associated with an increased risk of longterm mortality. 4 Balla et al 6 report on the long-term follow-up (median 46 months) of a group of 119 patients older than 70 years, admitted to hospital for pacemaker implantation and accurately evaluated with regard to frailty through the Short Physical Performance Battery (SPBB) test and handgrip test at discharge and 1-year follow-up. 6 A reduced performance at SPBB was quite common (71% of patients at discharge) and predictive of long-term mortality and the composite endpoint of hospitalization or death, even after adjustment for pertinent confounders at 1 year.…”
mentioning
confidence: 99%